2013
DOI: 10.1186/1999-3110-54-59
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and difference in vegetation structure of three desert shrub communities under the same temperate climate but with different microhabitats

Abstract: BackgroundCommunity structure and species composition are closely related to plant diversity and ecosystem stability. To explore the similarity in vegetation structure of shrub communities under the same temperate climate but with different microhabitats, 36, 28 and 13 sampling plots in Ephedra distachya, Seriphidium terrae-albae and Artemisia songarica communities were selected respectively, during the course of three seasons (early spring, summer, autumn) in Gurbantunggut Desert, north-western China. The spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…For example, Loera et al () found that species of Ephedra occurring in particularly arid environments tend to have papery‐bracted strobili, suitable for wind‐dispersal (Hollander & Vander Wall, ). This is consistent narrow microsite preferences of some desert species of Ephedra , such as E. distachya L. (of Asia), which occurs in slightly wetter areas around sand dune bases (Tao et al, ), and many North American species, which often occur on dune tops, where they may experience less competition and can utilize their long tap roots to access deep water resources (Ickert‐Bond, personal observation). However, additional studies of Ephedra and other species are needed to compare seed morphology, dispersal patterns, and distances from microsites to better understand the relationships between long distance dispersal in deserts and microsite preferences and access (e.g., Guo et al, ).…”
Section: Dispersal Hypotheses and Hypothesis Testing Within And Amongsupporting
confidence: 72%
“…For example, Loera et al () found that species of Ephedra occurring in particularly arid environments tend to have papery‐bracted strobili, suitable for wind‐dispersal (Hollander & Vander Wall, ). This is consistent narrow microsite preferences of some desert species of Ephedra , such as E. distachya L. (of Asia), which occurs in slightly wetter areas around sand dune bases (Tao et al, ), and many North American species, which often occur on dune tops, where they may experience less competition and can utilize their long tap roots to access deep water resources (Ickert‐Bond, personal observation). However, additional studies of Ephedra and other species are needed to compare seed morphology, dispersal patterns, and distances from microsites to better understand the relationships between long distance dispersal in deserts and microsite preferences and access (e.g., Guo et al, ).…”
Section: Dispersal Hypotheses and Hypothesis Testing Within And Amongsupporting
confidence: 72%
“…At the same time, high standard deviations indicate a high variability within each pasture due to varying topography and variability of rainfall. Nonetheless, the observed herbage offers were relatively low compared with studies in similar climatic contexts elsewhere (Sankey et al 2009;Behnke et al 2011;Sasaki et al 2012;Tao et al 2013), whereas the nutritive values were relatively high and constant throughout the studied years. Especially the latter observation is surprising, as in Central Asia the nutritive value of natural vegetation varies strongly with season and has been reported to be particularly low during winter and early spring (Yoshihara et al 2008;Glindemann et al 2009;Olson et al 2010;Sasaki et al 2012;Schönbach et al 2012;Bösing et al 2014;Ding et al 2014;Ma et al 2014;Müller et al 2014).…”
Section: Quantity and Quality Of Herbagementioning
confidence: 68%
“…A few similar studies have been carried out previously in this area (Tao et al, 2013;. Typically, in these studies, the vegetation type (or its floristic composition) changes markedly in different microhabitats.…”
Section: Discussionmentioning
confidence: 90%